1989
DOI: 10.1111/j.1399-302x.1989.tb00104.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subminimal inhibitory concentrations of antimicrobial agents on three bacterial mixtures

Abstract: A test tube technique was developed to screen bacterial mixtures to detect interbacterial interactions that play a role in determining sensitivity to antimicrobial agents. We found 3 mixtures where these bacterial interactions change the sensitivity to antimicrobials or change the proportions of each bacterial species in the mixture. The mixtures were: Fusobacterium nucleatum 102.3 and Bacteroides endodontalis ATCC 35406; F. nucleatum 102.3 and B. endodontalis BN11 a-f; and Capnocytophaga ochracea 1956c and Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…The reason for this delayed effect is not obvious. In vitro studies have suggested that the activity of "subminimal inhibitory concentrations" of metronidazole and other antibiotics against a mixed population of bacteria may be unpredictable due to metabolism of the drug by members of the flora (Lacroix & Mayrand 1989). However, it is less conceivable that such processes play a major role at the high concentrations obtained after topical application.…”
Section: I I Lmentioning
confidence: 99%
“…The reason for this delayed effect is not obvious. In vitro studies have suggested that the activity of "subminimal inhibitory concentrations" of metronidazole and other antibiotics against a mixed population of bacteria may be unpredictable due to metabolism of the drug by members of the flora (Lacroix & Mayrand 1989). However, it is less conceivable that such processes play a major role at the high concentrations obtained after topical application.…”
Section: I I Lmentioning
confidence: 99%
“…[10,11] In addition to A. actinomycetemcomitans, this combination is active against Treponema denticola, Tannerella forsythia, Porphyromonas gingivalis, Fusobacterium nucleatum, and Prevotella intermedia. [12][13][14] Azithromycin (AZT) is a macrolide antibiotic that has more potent activity against Gram-negative bacteria compared with erythromycin, can penetrate dental biofilms, and has good periodontal tissue penetration. [15][16][17][18] Higher concentrations persist in many tissues for 0-7 days using a simple dosage regimen.…”
Section: Introductionmentioning
confidence: 99%
“…In this combination, metronidazole, which metabolizes in liver where a highly effective hydroxymetabolite of the drug is produced, and amoxicillin synergistically act on A. actinomycetemcomitans , Treponema denticola , T. forsythia , and P. gingivalis 8,14,16,18‐20 . In addition to these species, Prevotella intermedia and Fusobacterium nucleatum have been shown to respond to metronidazole–amoxicillin combination 21,22 . Systemically administered amoxicillin and metronidazole and professional removal of supragingival plaque weekly for 3 months in patients diagnosed with refractory periodontitis results in stably low levels of periodontopathogens for 2 years 23 .…”
mentioning
confidence: 99%
“…8,14,16,[18][19][20] In addition to these species, Prevotella intermedia and Fusobacterium nucleatum have been shown to respond to metronidazole-amoxicillin combination. 21,22 Systemically administered amoxicillin and metronidazole and professional removal of supragingival plaque weekly for 3 months in patients diagnosed with refractory periodontitis results in stably low levels of periodontopathogens for 2 years. 23 These reports provide encouraging evidence for the polypharmaceutical use of adjunctive antibiotics in periodontal treatment.…”
mentioning
confidence: 99%